THE ADVANTAGES OF LEARNING ENGLISH THROUGH ENGLISH LITERATURE. - Xabibullayeva Gulsanam, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Learning  a  language  is  not  just  about  mastering  grammar  rules  and  expanding vocabulary; it is also about understanding the culture, emotions, and history behind the words. One of the most enriching ways to learn English is through its literature. English literature offers a window into the soul of the language, allowing learners to immerse themselves  in  its  beauty,  depth,  and  diversity.  Here  are  some  key  advantages  of learning English through literature: Firstly, English literature introduces learners to a vast array of words, phrases, and expressions  that  are often  absent  from  textbooks. Classic  works like  Shakespeare's plays or modern novels by authors such as Jane Austen and Charles Dickens are filled with poetic language and idiomatic expressions. For example, reading "To be, or not to be: that is the question" from Shakespeare's Hamlet not only teaches grammar but also helps learners appreciate the philosophical depth of the language.